2020
DOI: 10.1111/ijsw.12463
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term NEET among young adults with experience of out‐of‐home care: A comparative study of three Nordic countries

Abstract: Previous research suggests that young adults from out‐of‐home care (OHC) are at high risk of low education and unemployment. However, there are no studies on their risk of long‐term NEET (Not in Employment, Education or Training). This study compared the risk of NEET at age 21–23 among OHC youth across Denmark, Finland and Sweden, using register data for an entire birth cohort born in 1987. The Nordic countries share many features, but there are differences in the provision of after‐care support and in the lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 59 publications
3
10
0
Order By: Relevance
“…Furthermore, young people in the CEG were NEET in higher proportions (16% in the 18–21 age group). This agrees with the results of the longitudinal study conducted by Berlin et al (2021), in which they found that young people with out‐of‐home care experience were up to four times more likely to be long‐term NEET.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, young people in the CEG were NEET in higher proportions (16% in the 18–21 age group). This agrees with the results of the longitudinal study conducted by Berlin et al (2021), in which they found that young people with out‐of‐home care experience were up to four times more likely to be long‐term NEET.…”
Section: Discussionsupporting
confidence: 92%
“…There are some factors associated with the NEET status that are related to the organizational and work environment. As to the school environment, recent research from Nordic countries indicates that the excess risk for NEET can be attributed to teenagers' poor performance at school (Berlin et al 2020). While becoming NEET does not coincide with dropping out from high school, non-completion of school and entering the labor market without qualifications is a strong determinant of transitioning through the NEET condition, especially for women (Salvà-Mut et al 2016).…”
Section: Organizational and Work-related Factorsmentioning
confidence: 99%
“…The problems of NEET youth have been widely discussed among scientists and practitioners over the past decade (Balan, 2015;Henderson et al, 2017;Berlin et al, 2021). Such a group of people signals certain inefficiencies in the education system of a country and the labour market.…”
Section: Literature Reviewmentioning
confidence: 99%